Lithuanian Helsinky group documents to support decisions of Helsinky final act No. 17 - Knezys, Stasys (Genocidas ir rezistencija, 2025)
This document, dedicated to the International Year of the Child, refers to the lack of adequate conditions for children to grow up. It also recalls the occupation of Lithuania.
Keywords: Soviet occupation; human rights; civil resistance; Lithuanian Helsinky group